The Role of Financial Inclusion in Enhancing Social Justice - El-Nahal, Noha Mohamed Ibrahim (The Arab Journal of Administration, 2025)
This research aims to define the role of financial inclusion (FI) in enhancing social justice (SJ), by investigating FI principles and procedures’ impact on improving SJ criteria. The research also provides insights about setting extra FI procedures that can enhance SJ. Design/ Methodology/ Approach This research adopts an analytical descriptive approach to describe the features of both FI and SJ. Besides, it adopts the functional structural approach to explain the impact of FI principles (as the independent variable) on enhancing SJ criteria (as the dependent variable). Also, the research provides a theoretical framework by the author to illustrate the relationship between FI and SJ. The research sources are based on literature review, and secondary data sources including reports by WB, AFI, G20, OECD, and ESCWA. Findings Results show that FI principles when implemented in the financial system, can have a positive impact on SJ’s six criteria including poverty prevention, labor market inclusion, and access to education, providing health care, social cohesion and non-discrimination, and intergenerational justice which ensures good social and environmental conditions for future generations. Originality/ Value There is a lack of studies regarding the relations between FI and SJ enhancement. Therefore, the contribution of this research is filling in this gap in the literature, also the research provides a theoretical foundation for the relation between FI and SJ to assist policymakers to develop extra FI procedures that can impact positively on SJ.